Studi Ekonomi Media di CNN Indonesia TV: Eksistensi Pasar dan Strategi Pemasaran dalam Perspektif Ekonomi Media - Bagya Husna Fatwa; Gun Gun Heryanto; Busthomi Rifa'i; Suryadi Ali Wahyudi; Wildian Fajrin Nur Rahman (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This research discusses the dynamics of the media market in Indonesia with a focus on the case study of CNN Indonesia TV. The purpose of this research is to analyze the existence of the media market in Indonesia using a case study of CNN Indonesia TV. The purpose of this research is to analyze the existence of the media market in Indonesia using a case study of CNN Indonesia TV, as well as to understand how the media operates in an oligopolistic market structure, implements business strategies, and adapts to technological disruption through a media political economy theory approach. Using Robert G. Picard's media economy theory, this research examines how CNN Indonesia TV operates in an oligopolistic media market structure, implements its business strategy, and adapts to technological disruption. This research uses a descriptive qualitative approach with a case study method. The results show that CNN Indonesia TV maintains its existence through the utilization of global brand power, convergence to digital platforms, and innovative content strategies. These strategies enable CNN Indonesia TV to reach a wider audience and maintain commercial sustainability. This research contributes to the discourse of media economics and provides insights for media practitioners, policy makers, and researchers regarding the challenges and opportunities of the media industry in Indonesia.